A fifteenth-century fencing tournament in Strasburg - Olivier Dupuis (Bern Open Publishing, 2015)
An undated paper from the archives of Strasburg contains a set of rules approved by fencing masters for a fencing tournament. The dating of this document is uncertain but could be established around 1470-71. A complete and unpublished transcription will be supplied and completed with a detailed study of the final set of rules but also the subset which received some modifications. Even if some key points remains obscure, it's possible to find some comparison between this text and the contemporary knightly tournaments or the German Fechtschulen.